Coordination Scaffolds of Schiff Base Derived from Imatinib Amine: Synthesis, Spectroscopic and in vitro Biological Screening - Gajera, Prashant; Vadodaria, Milan; Parmar, Rahul (Indian Journal of Pharmaceutical Education and Research)
Aim: Imatinib amine based Schiff base heterochelates: Synthesis, Spectroscopic and in vitro biological screening. Materials and Methods: We acquired 2-Hydroxy-5-bromo benzaldehyde and 2-Hydroxy-5-nitro benzaldehyde from Sigma Ltd. (India). Purchased from Almon Industries in Ahmedabad, Gujarat, India, imatinib amine was utilised unpurified. Results: Elements C, H and N were elementally analysed using a Perkin-Elmer model 2400 elemental analyzer; 1H NMR spectra were obtained with an Advance 400 Bruker FT-NMR apparatus in DMSO-d6 solvent; FT-IR spectra were obtained as KBr pallets with a Nicolet-400D spectrophotometer; and the complex's FAB-mass spectrum was measured with a JEOL SX-102/DA-6000 mass spectrometer. Conclusion: As part of our present research, we are developing new Schiff's base ligands based on imitinib amine and their heterochelates with transition metals. All of the ligands and heterochelates that were synthesised were validated and characterised using 1H NMR, IR and mass spectrometry. Every synthesised chemical was tested for its ability to fight germs. The heterochelates have potent antibacterial action against Gram-positive (Staphylococcus epidermidis, Bacillus subtilis) and Gram-negative (Escherichia coli, Salmonella enterica) pathogens in contrast to their corresponding ligands. The heterochelates show significant effectiveness against one or more bacteria, so providing a new class of bactericidal drugs based on transition metals for investigation in the future.
Keywords: Antimicrobial studies; Imatinib amine; Schiff base; Spectroscopic studies; Transition metal-based coordination compounds.